2023
DOI: 10.1261/rna.079861.123
|View full text |Cite
|
Sign up to set email alerts
|

A tRNA-specific function for tRNA methyltransferase Trm10 is associated with a new tRNA quality control mechanism inSaccharomyces cerevisiae

Isobel E. Bowles,
Jane E. Jackman

Abstract: In Saccharomyces cerevisiae a single homolog of the tRNA methyltransferase Trm10 performs m1G9 modification on 13 different tRNAs. Here we provide evidence that the m1G9 modification catalyzed by S. cerevisiae Trm10 plays a biologically important role for one of these tRNA substrates, tRNATrp. Overexpression of tRNATrp (and not any of 38 other elongator tRNAs) rescues growth hypersensitivity of the trm10Δ strain in the presence of the antitumor drug 5-fluorouracil (5FU). Mature tRNATrp is depleted in trm10Δ ce… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Recently, a study reported a new tRNA quality control mechanism in S. cerevisiae , in which mature lacking m 1 G9 is eliminated by a Met22-dependent but RTD- and nuclear surveillance-independent degradation pathway ( Table 1 ) [ 93 ]. Further investigation is definitely needed to identify the nucleases responsible for this degradation and the molecular mechanisms of this intriguing tRNA quality control pathway.…”
Section: Influence Of Trna Core Modification On Trna Structure and St...mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a study reported a new tRNA quality control mechanism in S. cerevisiae , in which mature lacking m 1 G9 is eliminated by a Met22-dependent but RTD- and nuclear surveillance-independent degradation pathway ( Table 1 ) [ 93 ]. Further investigation is definitely needed to identify the nucleases responsible for this degradation and the molecular mechanisms of this intriguing tRNA quality control pathway.…”
Section: Influence Of Trna Core Modification On Trna Structure and St...mentioning
confidence: 99%
“…Further investigation is definitely needed to identify the nucleases responsible for this degradation and the molecular mechanisms of this intriguing tRNA quality control pathway. Interestingly, m 1 G9 prevents the degradation of , whereas its absence in has no effect on its cellular stability [ 93 ], adding to the list of known examples of tRNA core modifications that have different effects depending on the tRNA species and are only required for the cellular stability of a particular tRNA [ 72 ].…”
Section: Influence Of Trna Core Modification On Trna Structure and St...mentioning
confidence: 99%